2019
DOI: 10.1371/journal.pone.0214081
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic model assessment of adiponectin (HOMA-Adiponectin) as a surrogate measure of insulin resistance in adolescents: Comparison with the hyperglycaemic clamp and homeostatic model assessment of insulin resistance

Abstract: BackgroundStudies on adults have reported inverse association between the homeostatic model assessment (HOMA) of adiponectin (HOMA-Adiponectin) and the insulin resistance assessed by the glucose clamp technique. To our knowledge, in the pediatric population this association has not been previously investigated.ObjectivesTo evaluate the association between the HOMA-Adiponectin and the insulin resistance assessed by the glucose clamp technique in adolescents, and to compare the accuracy of HOMA-Adiponectin and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
1
11
1
1
Order By: Relevance
“…The ideal cut-off value for identifying MetS with the HOMA-AD index was ≥ 6.26. Contrary to our findings, Da Silva et al 32 found that the HOMA-AD (AUC, 0.712) had less detectable accuracy than HOMA-IR (AUC, 0.859). However, they also found that HOMA-AD could discriminate patients with and without IR as well as HOMA-IR.…”
Section: Discussioncontrasting
confidence: 99%
“…The ideal cut-off value for identifying MetS with the HOMA-AD index was ≥ 6.26. Contrary to our findings, Da Silva et al 32 found that the HOMA-AD (AUC, 0.712) had less detectable accuracy than HOMA-IR (AUC, 0.859). However, they also found that HOMA-AD could discriminate patients with and without IR as well as HOMA-IR.…”
Section: Discussioncontrasting
confidence: 99%
“…1,22 Researchers recommend the use of the HOMA-IR index to assess IR in epidemiological investigations. 5,23 However, there is no consensus in the literature regarding the cut-off point to use for adolescents, which leads to variations in the prevalence of IR reported. 1,5,24 In the present study, we adopted the 75 th percentile of the HOMA-IR index, which corresponded to 2.27.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this disorder affected more female adolescents in the present study, which is in agreement with the findings of other studies, despite the different cutoff points used for the HOMA-IR index. 1,22,23 The distinction in distribution between genders is due to differences in the changes in body composition between boys and girls and the action of hormones characteristic of the sexual maturation phase. 22 However, we found no significant association between the stages of sexual maturation and the HOMA-IR in the present study.…”
Section: 3%mentioning
confidence: 99%
“…In particular, changes in circulating concentrations of TNF-α, MCP1, and PDGF-BB were consistently correlated with IR in obese children. 67) Da Silva et al 70) examined the accuracy of HOMA-Adiponectin in detecting IR based on the hyperglycemic clamp technique in adolescents. Adiponectin increases fatty-acid oxidation in muscle and liver via activation of AMP-activated protein kinase and peroxisome proliferator-activated receptor alpha mediated by a specific receptor.…”
Section: Methods Of Measurement and Diagnosis Of Irmentioning
confidence: 99%